ANALISIS EFEKTIVITAS KERJA PEGAWAI BAGIAN ADMINISTRASI FISIP UNDIP - Maesaroh, Maesaroh (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2013)
Administration Section Fisip Undip was one part of conducting both administrative and academic, so itwas expected to assist the implementation of Tri Dhanna of Higher Education to effectively and efficiently. The problems were believed to often occur in the administration Fisip Undip include the uneven work load, duplication / twinningfonn, the existence of role ambiguity The things that allegedly led to less optimal effectiveness of employee activity was Good work was less clear, so often overlapping, supervision was less intense and less than optimal and less communication were good, especially the external / with stakholder, then the problem was fonnulated